A tutorial review of neural network modeling approaches for model predictive control - Ren, Yi Ming; Alhajeri, Mohammed S.; Luo, Junwei; Chen, Scarlett; Abdullah, Fahim; Wu, Zhe; Christofides, Panagiotis D. (Computers & chemical engineering, 2022)
An overview of the recent developments of time-series neural network modeling is presented along with its use in model predictive control (MPC). A tutorial on the construction of a neural network-based model is provided and key practical implementation issues are discussed. A nonlinear process example is introduced to demonstrate the application of different neural network-based modeling approaches and evaluate their performance in terms of closed-loop stability and prediction accuracy. Finally, the paper concludes with a brief discussion of future research directions on neural network modeling and its integration with MPC. •Review of neural network model approaches.•Training and parameter estimation of neural network models.•Neural network model performance evaluation and improvement.•Implementation in MPC and evaluation of closed-loop performance.